Pemberian Pinjaman Kredit dalam Perspektif Pemikiran Ekonomi Islam: Studi Kasus di Koperasi PNM mekar kutacane - Sophia Kharisah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The purpose of this article is to explain the credit system that exists at the moment. The method used is to study the theories of riba and its prohibitions contained in the Quran and Hadith. Through this study, it can be conceptually formulated Islamic economic practices, especially in terms of financing by buying and selling system. The results of the discussion showed that the Basic Rules of credit sales are allowed. Shaykh Ibn Usaimin said: buying and selling on credit is someone selling something (goods) at a certain price and immediately paying it off, this is allowed according to the original law in accordance with the command of Allah QS. Al-Baqarah: 282. In this case, the Medan City Government Civil Servant Cooperative (KPN Pemko Medan) in its work system has not been separated from ribawi elements that are not in accordance with Islamic economic principles.